Fundamentals of momentum, heat, and mass transfer - Welty, James R., 1933-; Rorrer, Gregory L., ....-; Wicks, Charles E., ....-; Wilson, Robert Elliott, 1937- (Chichester : Wiley, 2008)
The book provides a unified treatment of momentum transfer (fluid mechanics), heat transfer, and mass transfer. This new edition has been updated to include more coverage of modern topics such as biomedical/biological applications as well as an added separations topic on membranes. Additionally, the fifth edition focuses on an explicit problem-solving methodology that is thoroughly and consistently implemented throughout the text.· Chapter 1: Introduction to Momentum Transfer· Chapter 2: Fluid Statics· Chapter 3: Description of a Fluid in Motion· Chapter 4: Conservation of Mass: Control-Volume Approach· Chapter 5: Newton's Second Law of Motion: Control-Volume Approach· Chapter 6: Conservation of Energy: Control-Volume Approach· Chapter 7: Shear Stress in Laminar Flow· Chapter 8: Analysis of a Differential Fluid Element in Laminar Flow· Chapter 9: Differential Equations of Fluid Flow· Chapter 10: Inviscid Fluid Flow· Chapter 11: Dimensional Analysis and Similitude· Chapter 12: Viscous Flow· Chapter 13: Flow in Closed Conduits· Chapter 14: Fluid Machinery· Chapter 15: Fundamentals of Heat Transfer· Chapter 16: Differential Equations of Heat Transfer· Chapter 17: Steady-State Conduction· Chapter 18: Unsteady-State Conduction· Chapter 19: Convective Heat Transfer· Chapter 20: Convective Heat-Transfer Correlations· Chapter 21: Boiling and Condensation· Chapter 22: Heat-Transfer Equipment· Chapter 23: Radiation Heat Transfer· Chapter 24: Fundmentals of Mass Transfer· Chapter 25: Differential Equations of Mass Transfer· Chapter 26: Steady-State Molecular Diffusion· Chapter 27: Unsteady-State Molecular Diffusion· Chapter 28: Convective Mass Transfer· Chapter 29: Convective Mass Transfer Between Phases· Chapter 30: Convective Mass-Transfer Correlations· Chapter 31: Mass-Transfer Equipment
Keywords: Fluid mechanics; Heat -- Transmission; Mass transfer